A faultline in neoliberal environmental governance scholarship? Or, why accumulation-by-alienation matters. (June 2020) - Dunlap, Alexander; Sullivan, Sian
This article identifies an emerging faultline in critical geography and political ecology scholarship by reviewing recent debates on three neoliberal environmental governance initiatives: Payments for Ecosystem Services, the United Nations programme for Reducing Emissions from Deforestation and Forest Degradation in Developing Countries and carbon-biodiversity offsetting. These three approaches, we argue, are characterized by varying degrees of contextual and procedural – or superficial – difference, meanwhile exhibiting significant structural similarities that invite critique, perhaps even rejection. Specifically, we identify three largely neglected 'social engineering' outcomes as more foundational to Payments for Ecosystem Services, Reducing Emissions from Deforestation and Forest Degradation in Developing Countries and carbon-biodiversity offsetting than often acknowledged, suggesting that neoliberal environmental governance approaches warrant greater critical attention for their contributions to advancing processes of colonization, state territorialization and security policy. Examining the structural accumulation strategies accompanying neoliberal environmental governance approaches, we offer the term 'accumulation-by-alienation' to highlight both the objective appropriations accompanying Payments for Ecosystem Services, Reducing Emissions from Deforestation and Forest Degradation in Developing Countries and offsetting and the relational deficiencies accompanying the various commodifying instrumentalizations at the heart of these initiatives. We concur with David Harvey's recent work proposing that understanding the iterative and consequential connections between objective/material and subjective/psychological dimensions of alienation offers 'one vital key to unlock the door of a progressive politics for the future'. We conclude (with others) by urging critical geography and political ecology scholars to cultivate research directions that affirm more radical alternatives, rather than reinforcing a narrowing focus on how to improve Payments for Ecosystem Services, Reducing Emissions from Deforestation and Forest Degradation in Developing Countries and offsetting in practice.